Éducation aux données ou enseignement des données : quelles humanités numériques au lycée ? - Béatrice Drot-Delange; Françoise Tort (Humanités Numériques)
Data lies at the heart of the digital society. Their growing importance leads us to believe that data education is essential. It can be considered as one of the pillars of digital humanities education. The curricula for digital sciences and technology (SNT) in tenth grade in France (first year of the lycée) include teaching data. We seek to know how it contributes to data education. We are conducting an analysis of the SNT curriculum and textbooks in the light of the model of data education proposed by researchers in computer science education. Our results show that this teaching subject has limited contribution to data education, particularly in its analytical and critical dimensions.